Peran Home Industry Dalam Peningkatan Ekonomi Keluarga Ditinjau Dari Ekonomi Islam (Studi Kasus Home Industri Madura Koong) - Nur Islamiya; DEWI VAHLEVI (ICO EDUSHA, 2022)
Koong Madura home industry is a business that produces bird feed. Madura koong itself has been producing feed for turtledoves, cendets, lovebirds, and canaries. Madura koong itself has become a pioneer in the business of other bird feeds because it uses high-quality raw materials. This home industry itself already has 4 branches, apart from that for distribution it has reached abroad. The purpose of this study is to determine the role of home industry in improving the family economy in terms of Islamic economics. The research method used is descriptive qualitative research. The research techniques used are interviews and observation. Keywords: Role Of The Home Industry, family economic improvement, Economic Islam References Harmonis, R. (2021). Efektivitas Home Industry Dalam Meningkatkan . Ekonomi Syariah, 103-105. Susana, S. (2011). Peranan Home Industri Dalam Meningkatkan. Ekonomi Syariah, 2-7. Vioriska, E. N. (2019). Peran Home Industry Terhadap Ekonomi. Ekonomi Syariah, 72-121.